THE QUALITY OF AUCTION SERVICES AT THE STATE ASSETS AND AUCTION SERVICE OFFICE (KPKNL) MALANG - Novianto, Catur Eko; Suryadi, Suryadi; Yumarni, Tri (Erudio Journal of Educational Innovation, 2026)
Public services, particularly auction services at KPKNL Malang, still face various challenges such as a high volume of requests that is not proportional to service capacity, limited human resources, and technical issues in digital systems. These conditions lead to service delays, overload, and suboptimal service quality, ultimately affecting public satisfaction. This study aims to analyze the quality of auction services at KPKNL Malang and to formulate effective and efficient strategies for service improvement. The research employs a descriptive method with a qualitative approach through interviews, and analysis is conducted using the SERVQUAL concept and SWOT analysis. The results show that the overall quality of auction services is fairly good but not yet optimal, particularly in terms of reliability and service consistency. Supporting factors include strong organizational commitment, competent human resources, and technological support, while inhibiting factors include limited staff, high workload, and technical system constraints. The SWOT analysis places KPKNL Malang in an aggressive quadrant, indicating that the appropriate strategy is to leverage internal strengths to maximize external opportunities through improving human resource capacity, optimizing digital technology, and developing more transparent, efficient, and customer-oriented service innovations.